2021
DOI: 10.1186/s13068-021-02034-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of seven industrial anaerobic digesters supplied with biochar

Abstract: Background Recent research articles indicate that direct interspecies electron transfer (DIET) is an alternative metabolic route for methanogenic archaea that improves microbial methane productivity. It has been shown that multiple conductive materials such as biochar can be supplemented to anaerobic digesters to increase the rate of DIET. However, the industrial applicability, as well as the impact of such supplements on taxonomic profiles, has not been sufficiently assessed to date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Therefore, future research should focus on supplementing microbiology consortium with mutual relationships. Heitkamp et al (2021) found that the concentration of microorganisms attached to biochar was higher than the average concentration of suspended and attached growth microorganisms. This means that biochar can be used as a carrier for microorganisms to alleviate ammonia inhibition and is an ideal partner for bioaugmentation.…”
Section: The Potential Application Mode Of Biochar In Relieving Ammon...mentioning
confidence: 95%
“…Therefore, future research should focus on supplementing microbiology consortium with mutual relationships. Heitkamp et al (2021) found that the concentration of microorganisms attached to biochar was higher than the average concentration of suspended and attached growth microorganisms. This means that biochar can be used as a carrier for microorganisms to alleviate ammonia inhibition and is an ideal partner for bioaugmentation.…”
Section: The Potential Application Mode Of Biochar In Relieving Ammon...mentioning
confidence: 95%
“…Lower Simpson (2.5) and Shannon (0.6) index values were observed in the enriched culture, evidenced by the distributions of the selected community dominance that drives the specific metabolic reactions. Low variance and evenness distributions of the carboxydotrophic microbes account for the specific acetogenic and solventogenic process in which syngas feedstock converted into the WLP pathway metabolites account for the microbiome assisting the dominant growth of the specific microbiome (C1-fixing) [ 43 ]. Cho1 and abundance-based coverage estimators (ACE) species richness was depicted in the median of 530 and 480, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a relative accumulation was still observed in the upstream substances’ (propionic acid, butyric acid) concentration under high ammonia concentration. Furthermore, the pH of all reactors varied within a narrow range from 8.4 to 8.9 (Figure S2), which is the range in which most actual AD plants operate and is an appropriate range for methanogen growth. , The reason for the comparatively stable pH is the synchronous change in TAN, which has the function of buffering and neutralizing the acid. However, the stability in this case is not synonymous with reaching sufficiently good performance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the biochar addition method reported by existing studies still primarily started from the initiation of fermentation rather than being targeted at the stage of a failed methanization, making it difficult to identify whether it can be regarded as an antidote for emergency intervention to alleviate the inhibited steady state. Although there have been a few studies exploring the application of biochar in a full-scale plant or in a failed digester, both focused on the single acid stress and planktonic microorganisms existing in the digesters, leading to the primary functional microorganisms potentially promoted by the added biochar still remaining elusive. Moreover, existing studies relating to biochar-associated biofilms merely focused on microbial diversity instead of the amount of microorganisms …”
Section: Introductionmentioning
confidence: 99%